RESPONSE SOME QUALITY CHARACTERISTICS OF SUNFLOWER (Helianthus annuus L.) VARIETY TO ZINC SPRAYING - Alsubaihi, Sufyan Munther; Al-Ani, Muaiad H. (Diyala Agricultural Sciences Journal, 2020)
A field experiment was carried out in the Spring and Autumn seasons of 2018 in Al-Subaihat village (latitude 33° 21- N and longitude 43° 46- E) Fallujah city - Al-Anbar governorate in silty-loam soil. To study the effect of two factors which were foliar zinc application different concentration of zinc 0, 0.5, 1.0 and 1.5 kg Zn h1 in the form of aqueous zinc sulfate ZnSO4.7H2O (46% Zn) on the Qualitative Characteristics of three varieties of sunflower (Tarsan8018, Esahaqi 1 and Aqmar). The layout of experiment RCBD ,arrangemental in Factorial experimental units distributed (36 experimental units) with three replicates. The results showed significant different between cultivars in most of the studied traits. Aqmar gave the highest oil content of 54.14 and 51.40% for the both spring and autumn respectively. For the autumn season, Tarsan1018 cv. recorded highest mean percentage of unsaturated fatty acids in seeds about 91.73% for spring season, While Isahaqi 1 exceeded the highest mean of 90.91% for autumn season. Isahaki 1 plants recorded the highest average carbohydrate percentage of 14.70 and 14.97% Zinc spraying resulted in a significant increase in the seed oil percentage. The concentration of 1.5 kg Zn h-1 achieved the highest mean ( 51.56% ) in spring season , while concentration of 1.0 kg Zn E-1 achieved the highest mean capacity in the autumn season (48.79%) Concentration 0.5 kg Zn h-1 are highest percentage of unsaturated fatty acids was 91.01%. In the autumn season, while the concentration of 1.0 kg Zn h-1 achieved the highest average percentage of unsaturated acids in seeds was 90.56%, also the concentration of 1.0 kg Zn h-1 gave the highest percentage of oleic acid in oil was 68.48% and 27.92% for the two season respectively.